EP.FRI.815 Hartmann's at 100: Relevant or Redundant?. (28th October 2021) - Frakas, Nicholas; Conroy, Michael; Harris, Holly; Kenny, Ross; Baig, Mirza
Abstract: Introduction: Henri Albert Hartmann first described resection of the rectosigmoid colon and exteriorization of the bowel with a colostomy in 1921. As we approach the centenary anniversary of Hartmann's procedure we feel it is the appropriate time to discuss this significant surgical advancement and its relevance in modern day surgery.    Methods: We provide a contemporary overview of the literature, highlighting various aspects of the Hartmann's procedure applicable to both today's clinical practice and that of tomorrow. Results: Hartmann's procedure was initially performed for colorectal carcinoma in 1921. One hundred years on, the Hartmann's procedure remains a safe and effective option in select patients with colorectal cancer and at high risk of anastomotic failure. In recent years, the majority of Hartmann's procedures have been performed for benign disease and the majority of these cases are in the emergency setting. As hospital admissions with acute diverticulitis continue to rise steeply, the importance of the Hartmann's procedure in the field of surgery continues. Hartmann's procedure has adapted as surgery has advanced. Hartmann's is now performed both laparoscopically and robotically with good postoperative outcomes.   Conclusions: In 1921, few would have predicted how modern day medicine and surgery is today. Hartmann's procedure has survived the surgical test of time, and its key principles remain the same. As we look to the future, it is unlikely that it's role will be lost to surgical advances, but to alternative management modalities in disease prevention.